Resected case of stage IV pleomorphic carcinoma of the lung with long-term survival - Haruki Choshi; Mototsugu Watanabe; Hiroyuki Ujike; Yumiko Sato; Toshiaki Morito; Ryujiro Sugimoto; Kazuhiko Kataoka (Surgical Case Reports, 2020)
Abstract Background No established treatments for pulmonary pleomorphic carcinoma exist because of its rarity, and the prognosis is poorer than that of other non-small cell lung cancers. Case report We present a case of stage IV pleomorphic carcinoma; the patient was a 66-year-old male. He was referred to our hospital because of a right adrenal hemorrhage and a lung tumor. A systemic examination revealed that the lung tumor was a primary lung cancer and that the adrenal hemorrhage was due to a metastatic cancer. We performed an adrenalectomy and resection of the lung tumor and obtained a diagnosis of pleomorphic carcinoma with adrenal metastasis. The patient has remained recurrence-free for 6 years since the surgery. Conclusions We report a patient with stage IV pleomorphic carcinoma of the lung and an oligometastasis in whom a complete resection enabled a good outcome. Additional reports are needed to clarify definite prognostic factors and the optimal treatment for pleomorphic carcinoma.